Feasibility of Intravenous Gemcitabine and an Intraperitoneal Platinum Agent in the Treatment of Ovarian Cancer - Giuntoli, R.L. (J Chemother, 2011)
The goal of this study is to determine the feasibility of intravenous gemcitabine and an intraperitoneal platinum agent in the treatment of patients with ovarian cancer. We performed a retrospective chart review of patients with primary, persistent or recurrent ovarian cancer, who received intravenous gemcitabine and an intraperitoneal platinum agent. Patients received gemcitabine (750 mg/m(2)) intravenous on days 1 and 8 and cisplatin (100 or 60 mg/m(2)) intraperitoneal on day 1 every 21 - 28 days. An alternate regimen was composed of gemcitabine (750 mg/m(2)) intravenous and carboplatin (AUC 5) intraperitoneal on day 1 every 21 days. Dose reductions occurred at the discretion of the prescribing physician. Intravenous gemcitabine and an intraperitoneal platinum agent were administered to 12 patients with advanced primary or recurrent ovarian cancer. Myelosuppression was the most common toxicity. Grade 3 or 4 thrombocytopenia, neutropenia and anemia occurred in 7, 8 and 2 patients respectively. Dose reductions were required in 7 of 12 patients. 10 of 12 patients received 6 cycles of the regimen. Treatment was discontinued prior to 6 cycles in 2 of 12 patients secondary to progression in one case and to grade 4 neutropenia and thrombocytopenia in another. The combination of intravenous gemcitabine and an intraperitoneal platinum agent appears to be a feasible regimen in patients with ovarian cancer. The most common toxicity was myelosuppression, which resulted in dose reductions in almost half of the patients.